Proliferation and differentiation of circulating haemocytes of Ruditapes philippinarum as a response to bacterial challenge. Issue 81 (October 2018) - Cima, Francesca; Matozzo, Valerio
Abstract: Ultrastructural investigation confirmed the presence of four cell types (granulocytes, hyalinocytes, serous cells, and haemoblasts) in the haemolymph of the Manila clam, Ruditapes philippinarum . Granulocytes were characterised by numerous electron-dense granules, whereas hyalinocytes had a considerable number of small clear vesicles. Serous cells exhibited large vacuoles, which filled the cytoplasm, and haemoblasts (the undifferentiated cells) were small roundish cells characterised by a high nucleus/cytoplasm ratio. The presence of circulating haemoblasts was observed at various phases of mitosis. Updated data concerning the proliferation and differentiation of circulating haemocytes were obtained after both in vitro and in vivo bacterial challenge. The results demonstrated that cell proliferation occurred within 15 h of exposure, and most haemocyte types responded to the stimuli. The number of granulocytes significantly decreased after massive phagocytosis and ultrastructural observations confirmed that they were active phagocytic cells against both Gram-positive and Gram-negative bacteria, which were rapidly engulfed into large phagosomes. Granulocyte lysis may represent a protection response against bacterial proliferation inside phagosomes. The number of serous cells significantly increased, suggesting a previously unreported pivotal immune role during bacterial infection. A panel of lectins was used as probes to further characterise haemocytes and their relationships. Only hyalinocytes were not positive for the lectins assayed, whereas all lectins labelled serous cells, suggesting that these cells have a variety of specific carbohydrates, which are shared with certain haemoblasts. The hypothesis of the existence of a prospective haemoblast for serous cell origin is discussed. Highlights: Circulating haemocytes proliferate and differentiate after in vitro and in vivo infection. The presence of circulating haemoblasts was observed at various phases of mitosis. Cell proliferation occurs within 15 h of exposure and haemocyte composition varies. Cell differentiation has been investigated with a selected panel of lectins. The number of serous cells significantly increases suggesting an unknown immune role.